Is Taiwan Chinese? : the impact of culture, power, and migration on changing identities - Brown, Melissa J. (Berkeley series in interdisciplinary studies of China ;, 2004)
In a unique comparison of studies drawn from both Taiwan and China, Brown's book shows how identity is shaped by social experience - not culture and ancestry, as is commonly claimed in political rhetoric.